2011
DOI: 10.1088/0957-4484/22/14/145306
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of cone-shaped boron doped diamond and gold nanoelectrodes for AFM–SECM

Abstract: We demonstrate a reliable microfabrication process for a combined atomic force microscopy (AFM) and scanning electrochemical microscopy (SECM) measurement tool. Integrated cone-shaped sensors with boron doped diamond (BDD) or gold (Au) electrodes were fabricated from commercially available AFM probes. The sensor formation process is based on mature semiconductor processing techniques, including focused ion beam (FIB) machining, and highly selective reactive ion etching (RIE). The fabrication approach preserves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…In the subsequent RIE etching step, only SF 6 is used to etch Si 3 N 4 selectively, exposing the conductive tip, whereby the Cr layer protects the rest of the sample as shown in Figure 1c. The removal of the insulation layers Overall, we fabricated more than 30 devices for field emission as well as electrochemical investigations [10], demonstrating the versatility of this approach. With respect to the miniaturized vacuum gauges, we fabricated four devices with a cathode-anode spacing of about h=500 nm, and two devices with a spacing of about 1 µm.…”
Section: Methodsmentioning
confidence: 90%
“…In the subsequent RIE etching step, only SF 6 is used to etch Si 3 N 4 selectively, exposing the conductive tip, whereby the Cr layer protects the rest of the sample as shown in Figure 1c. The removal of the insulation layers Overall, we fabricated more than 30 devices for field emission as well as electrochemical investigations [10], demonstrating the versatility of this approach. With respect to the miniaturized vacuum gauges, we fabricated four devices with a cathode-anode spacing of about h=500 nm, and two devices with a spacing of about 1 µm.…”
Section: Methodsmentioning
confidence: 90%
“…The difference between I d,calc and I d,exp could be related to unavoidable errors upon estimation of the geometric parameters, as well as to deviations of the tip shapes from an ideal one [33]. For comparison, I d,calc ≈ 4 × I d,exp was previously obtained for another Au-coated tip [32]. We believe that the removal of titanium oxide from the gold tip, as implemented in our new experiments, comprises the critical step to obtain a better agreement between calculated and experimental currents.…”
Section: Fabrication and Electrochemical Characterization Of The Insumentioning
confidence: 96%
“…Based on cyclic voltammetry, we demonstrated that these probes have well-defined conductive tips [32]. Later we carried out a detailed investigation of the insulation (leakage and stability) of the entire chip by a step-wise immersion of the probe into the solution ( figure 3).…”
Section: Fabrication and Electrochemical Characterization Of The Insumentioning
confidence: 99%
See 1 more Smart Citation
“…A potential is applied between the working and reference electrode that is sufficient to oxidize or reduce a species of interest in solution as the probe operates in contact-AFM mode. A number of SECM-AFM probes, which contain gold [2], platinum [1], carbon nanotubes [3], and borondoped diamond [4,5] as electrode material, have been demonstrated previously. An area that SECM-AFM has yet to be applied is for the detection of neurological species in situ.…”
mentioning
confidence: 99%